2002
DOI: 10.1360/02yc9057
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence in map positions between pathogen-induced defense-responsive genes and quantitative resistance loci in rice

Abstract: Quantitative disease resistance conferred by quantitative trait loci (QTLs) is presumably of wider spectrum and durable. Forty-four cDNA clones, representing 44 defense-responsive genes, were fine mapped to 56 loci distributed on 9 of the 12 rice chromosomes. The locations of 32 loci detected by 27 cDNA clones were associated with previously identified resistance QTLs for different rice diseases, including blast, bacterial blight, sheath blight and yellow mottle virus. The loci detected by the same multiple-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Wang et al (2001) reported that the locations of several rice ESTs (expressed sequence tags) with defense-response gene-like sequences were associated with previously identified resistance QTLs for rice diseases. Xiong et al (2002) showed that the locations of more than 20 defense-responsive genes induced by pathogen infection were near resistance QTLs for different rice diseases. In this study, the chromosomal locations and pathogen specificities of seven sequences, EI12I1, BI26N5, EI35I3, EI1K8, EI10P9, EI5P11 and EI13J2, corresponded well with those of previously identified blast resistance QTLs (Wang et al 1994;Chen et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2001) reported that the locations of several rice ESTs (expressed sequence tags) with defense-response gene-like sequences were associated with previously identified resistance QTLs for rice diseases. Xiong et al (2002) showed that the locations of more than 20 defense-responsive genes induced by pathogen infection were near resistance QTLs for different rice diseases. In this study, the chromosomal locations and pathogen specificities of seven sequences, EI12I1, BI26N5, EI35I3, EI1K8, EI10P9, EI5P11 and EI13J2, corresponded well with those of previously identified blast resistance QTLs (Wang et al 1994;Chen et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The triangles in the bacterial blight resistance and blast resistance QTLs, detected using the same population as was used to construct the framework map, indicate the logarithm-of-odds peaks of the resistance effects. The filled circles represent the centromeric regions identified previously (Wang et al 2000a) co-localize with resistance QTLs identified in barley, bean, rice and potato (Faris et al 1999;Geffroy et al 2000;Trognitz et al, 2002;Xiong et al 2002;Ramalingam et al 2003). Thus, the candidate-gene approach may provide a means for pinpointing the genes that underlie resistance QTLs.…”
Section: Analyses Of the Sequences And Expression Patterns Of Defensementioning
confidence: 99%
“…Recent studies have shown that some defense-responsive genes are located in the vicinity of quantitative trait loci (QTLs) for disease resistances in different plant species (Faris et al 1999;Wang et al 2001;Xiong et al 2002;Ramalingam et al 2003;Wen et al 2003). QTLs for quantitative disease resistance are generally considered to be valuable sources of broad-spectrum and durable resistance in rice breeding programs (Roumen 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, large numbers of defense-responsive genes have been identified to be involved in the incompatible interaction between rice and Xoo or M. grisea (Zhou et al, 2002;Chu et al, 2004). However, the impact of each of these defenseresponsive genes on rice disease resistance is unknown, except for the knowledge that some of these genes colocalize with quantitative trait loci (QTLs) for rice disease resistance (Wang et al, 2001;Xiong et al, 2002;Ramalingam et al, 2003;Wen et al, 2003;Chu et al, 2004). Thus, the values of these genes in the improvement of disease resistance for rice breeding need to be explored.…”
Section: Introductionmentioning
confidence: 99%